Comparative efficacy and safety of neoadjuvant radiotherapy for patients with borderline resectable, and locally advanced pancreatic ductal adenocarcinoma: a systematic review and network meta-analysis protocol. Issue 7 (13th July 2022) - Lv, Wanrui; Wang, Qingfeng; Hu, Qiancheng; Wang, Xin; Cao, Dan
Abstract : Introduction: The optimal dose and treatment modality of neoadjuvant radiotherapy applied for treating borderline resectable and locally advanced pancreatic ductal adenocarcinoma (PDAC) have been debated topics in oncology. The objective of the present network meta-analysis (NMA) is to study and compare the efficacy and safety of neoadjuvant radiotherapy comprehensively using different doses in patients with borderline resectable pancreatic cancer (BRPC) and locally advanced pancreatic cancer (LAPC). Methods and analysis: Four electronic databases, including PubMed, EMBASE, Cochrane library and Web of science, will be searched thoroughly to identify relevant studies published from 2006 to October 2020. Electronic searching by titles using neoadjuvant treatments for PDAC will be performed in the annual meetings of European Society of Medical Oncology and American Society of Clinical Oncology (2018–2020). ClinicalTrials.gov will also be searched for grey literature. Two reviewers will perform search strategies and extract data independently. R0 resection rate and local control rate are defined as primary outcomes. Secondary outcomes include overall survival, disease-free survival and acute and late grade 3 and grade 4 toxicities. For randomised control trials, the risk of bias will be assessed using the Cochrane Risk of Bias Tool, while the risk of bias for non-randomised, observational studies will be evaluated using the Risk Of Bias In Non-randomised Studies-of Interventions. The quality of evidence will be evaluated using the version of Cochrane tool and Grades of Recommendation, Assessment, Development and Evaluation. Subgroup analysis and sensitivity analysis will be conducted in the present NMA. Ethics and dissemination: This study will synthesise the evidence regarding dose schedule of neoadjuvant radiotherapy in patients with BRPC and LAPC. We hope the findings from this NMA will help clinicians and patients select the optimal modality and dose schedule of neoadjuvant radiotherapy with respect to patient-reported outcomes. As no primary data collection will be undertaken, no ethics approval is required. The results will be disseminated through peer-reviewed journal. PROSPERO registration number: CRD42020222408.